USE OF 20 MINUTE WHOLE BLOOD CLOTTING TIME IN PATIENTS OF SNAKEBITE; AN EXPERIENCE FROM KOHAT, KHYBER PAKHTUNKHAH: Blood Clotting Time in Patients of Snakebite - Javed, Hammad; Bashir, Tariq; Rauf, Atif; Murtaza, Syed; Jibran, Raja (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the diagnostic accuracy of 20-minute whole blood clotting time in hemotoxic snakebite.Study Design: Cross sectional validation study.Place and Duration of Study: Combined Military Hospital Kohat Pakistan, from Jul 2015 to Jun 2017.Methodology: Study included 52 patients who presented with the complaint of a snakebite. The data was recorded on predesigned proforma including clinical, laboratory features. All the patients were kept indoor for observation for a minimum of 72 hours from the time of presentation.Results: The study showed that males were more affected with age group between 20-50 years. Most common presenting features were local swelling 33 (71%) and pain and most common snakebite type was hemotoxic 33 (71%). The 20-minute whole blood clotting time was found to have low sensitivity (61%) and specificity (58%). A significant association was found between the dose of anti-snake venom and severity of coagulopathy (p